Historical Evolution of the Conception of Disaster Risk Management: some Considerations - Rosales-Veítia, José (2021)
Just as science has advanced by leaps and bounds since the second half of the twentieth century, today what is known as risk management has gone through a profound conceptual as well as experimental transformation, which is why it is currently being investigated mainly from the social disciplines. Currently, this scientific discipline seeks to build a balanced relationship between the environment and human society. There are countries that have taken the lead on the issue, which allows us to see that it is viable to advance to a better world. The present monograph is a documentary review on the paradigmatic conception of risk management through history and the basic conceptual postulates of it. The main conclusions are: today, risk management has gone from reactively attending adverse events to educating the population to reduce risks; In addition, in order to achieve good results in risk management, it is necessary to empower the population most exposed to the occurrence of adverse events.